Investigation of the effect of pressure on some physical parameters and thermoelastic phase transformation of NiAl alloy - Kazanc, Sefa; Tatar, Cengiz (Pergamon-Elsevier Science Ltd, 2008)
The Ni-Al alloys which exhibit the thermoelastic phase transformations in the composition range from 60 to 65 atomic percentage of Ni are widely used in the high technology applications. In this study, thermoelastic phase transformations of Ni-37.5 at.% Al alloys at 0, 1 and 2 GPa pressures were investigated by using MD simulation. Physical interactions among atoms in the alloy system were modelled using Sutton-Chen version of the embedded atom method based on many-body interactions. The potential parameters for cross interactions between Ni and Al atoms were estimated by optimising the results obtained from the molecular dynamics simulations. Moreover, the effect of applied pressure on transformation temperatures, enthalpy, entropy and elastic energy of model alloy system were investigated. The obtained result showed that the transformation temperature increased with applied pressure while enthalpy, entropy and elastic energy decreased. The values of the thermodynamical parameters that obtained in this study are in very good agreement with results of experimental studies. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: thermoelastic phase transformation; embedded atom method; molecular dynamics simulation; elastic energy; enthalpy; Ni-Al alloy